Esprits « convergents » ou « divergents » : tradition et enseignement scientifique chez Thomas Samuel Kuhn et Karl Popper - Alain Firode (Recherches en Éducation)
This paper aims to compare the positions of T.S Kuhn and K. Popper in science education. Kuhn’s conclusions on this subject are clearly in support of traditional pedagogical methods: because the practice of science, according to him, requires "converging" minds, working within the framework of a "paradigm", the formation of future scientists must be the result of dogmatic teaching, encouraging students to accept the knowledge that is currently available. Popper's position, on the contrary, is more difficult to define: while considering, against Kuhn, that the researcher must have a "divergent" mind, inclined to challenge established knowledge, the philosopher nevertheless recognizes that research and scientific teaching have a necessary and legitimate part of dogmatism and conservatism.